1996
DOI: 10.1002/(sici)1097-4636(199604)30:4<523::aid-jbm11>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Light and electron microscopic studies of bone‐titanium interface in the tibiae of young and mature rats

Abstract: Bone-titanium contact was examined in young and mature rats on various days after insertion of pure titanium into the tibia. Under light microscopy, on the 14th day, lamellar mature bone was initially formed, and was seen to make direct contact with the titanium in both groups. In young rats on the 28th day, bone-titanium contact was greater than that in mature animals. On I-pm sections, an amorphous zone 0.5-1.0 p m thick was found around the titanium, and a slender cell layer lay parallel to the implant, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
26
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 0 publications
6
26
0
Order By: Relevance
“…In addition, this lamina limitans seems to consist of osteopontin and α2 HS-glycoprotein [28]. Recently, osteoblast-like cells made direct contact with titanium via a 20-50 nm thin amorphous zone is shown [29]. A 20-50 nm thin amorphous zone, a slender cell layer, and/or a poorly mineralized zone were interposed between bone and titanium.…”
Section: Nanometer-level Interface Structuresupporting
confidence: 86%
“…In addition, this lamina limitans seems to consist of osteopontin and α2 HS-glycoprotein [28]. Recently, osteoblast-like cells made direct contact with titanium via a 20-50 nm thin amorphous zone is shown [29]. A 20-50 nm thin amorphous zone, a slender cell layer, and/or a poorly mineralized zone were interposed between bone and titanium.…”
Section: Nanometer-level Interface Structuresupporting
confidence: 86%
“…Murai et al 45 also reported that osteoblasts were in direct contact with the titanium surface via a thin amorphous zone formed on slender osteoblast-like cells. In this study, the osteoblasts formed close and perpendicular contact with the zirconia-implant surface, and their reactivity to the zirconia implant was similar to that to the titanium implant.…”
supporting
confidence: 56%
“…Therefore, it is considered to be important to confirm whether or not the amorphous layer (zone) really contains GAGs. Thus, the aims of the present study are 1) to ultrastructurally observe the interface, in particular the amorphous zone, between the bone and coated titanium in 6-week-old rats on the 28th day after the insertion of the titanium (the use of these rats is based on the data obtained from previous studies [8,12,22] in which the bone-implant contact was found to reach a maximum on the 28th day), 2) to identify the presence of the ruthenium red-positive amorphous zone, and 3) to compare the differences between the bone-coated titanium interface and the bone-titanium rod interface.…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, Listgarten et al [11] did not show the presence of such an amorphous layer (zone), whereas Serre et al [18] reported the interposition of a loose extracellular matrix with fibrillar or non fibrillar materials instead of an amorphous layer (zone). Thus, although the findings regarding the presence of an amorphous layer remain controversial, we support the presence of an amorphous layer (zone), because we recently found a 20-40 nm-thick amorphous zone at the bone-titanium interface [12]. Unfortunately, the method used in this study has one main drawback; the titanium rod must be removed from the bone since it is impossible to directly cut the titanium rod-containing specimens, and such detachment of the implant from the specimen may possibly destroy the bone-titanium interface.…”
Section: Introductionmentioning
confidence: 99%